Antithrombotic treatment and outcome after endovascular treatment and acute carotid artery stenting in stroke patients with atrial fibrillation - Johannes M. Weller; Franziska Dorn; Julius N. Meissner; Sebastian Stösser; Niklas M. Beckonert; Julia Nordsiek; Christine Kindler; Christoph Riegler; Fee Keil; Gabor C. Petzold; Felix J. Bode; the GSR-ET investigators (Neurological Research and Practice, 2022)
Abstract Background Oral anticoagulation (OAC) is the mainstay of secondary prevention in ischemic stroke patients with atrial fibrillation (AF). However, in AF patients with large vessel occlusion stroke treated by endovascular therapy (ET) and acute carotid artery stenting (CAS), the optimal antithrombotic medication remains unclear. Methods This is a subgroup analysis of the German Stroke Registry—Endovascular Treatment (GSR-ET), a prospective multicenter cohort of patients with large vessel occlusion stroke undergoing ET. Patients with AF and CAS during ET were included. We analyzed baseline and periprocedural characteristics, antithrombotic strategies and functional outcome at 90 days. Results Among 6635 patients in the registry, a total of 82 patients (1.2%, age 77.9 ± 8.0 years, 39% female) with AF and extracranial CAS during ET were included. Antithrombotic medication at admission, during ET, postprocedural and at discharge was highly variable and overall mortality in hospital (21%) and at 90 days (39%) was high. Among discharged patients (n = 65), most frequent antithrombotic regimes were dual antiplatelet therapy (DAPT, 37%), single APT + OAC (25%) and DAPT + OAC (20%). Comparing DAPT to single or dual APT + OAC, clinical characteristics at discharge were similar (median NIHSS 7.5 [interquartile range, 3–10.5] vs 7 [4–11], p = 0.73, mRS 4 [IQR 3–4] vs. 4 [IQR 3–5], p = 0.79), but 90-day mortality was higher without OAC (32 vs 4%, p = 0.02). Conclusions In AF patients who underwent ET and CAS, 90-day mortality was higher in patients not receiving OAC. Registration: https://www.clinicaltrials.gov ; Unique identifier: NCT03356392.